The Effect of Happiness at Work Towards Internal Branding Mechanism: A Case Study on Kita Berkisah (Journal of Business and Management, 2021)
Kita Berkisah is mental health care organization that provides e-counselling session, peer support group, and online talks. Since it has been established for a year, in order to keep growing, they feels the need to continuously provide the best service for individuals who need a safe space for healing both customers and the people inside. To help customers find positive vibes, they also need to ensure the employee initiate brand aligned behaviour through internal branding mechanism (IBM). This study objectively find the influence of the employee’s positive feelings from the constructs of happiness at work (HAW) towards brand understanding and brand commitment in IBM. A quantitative survey was conducted among 52 employees. The result indicate happiness at work has a positive and significant influence to both brand understanding and commitment. It further shows that work engagement as one of the construct of HAW has the most significant influence towards brand understanding and commitment. This study implies that Kita Berkisah could firstly focus on building work engagement to develop employee’s brand aligned behaviour. HAW is expected to be explored to improve IBM for academic and management implications.Keywords: Happiness at Work (HAW); Internal Branding Mechanism (IBM); Brand Understanding; Brand Commitment.